Resisting the Urge to Smoke and Craving during a Smoking Quit Attempt on Varenicline: Results from a Pilot FMRI Study. (March 2013) - Hartwell, Karen J.; LeMatty, Todd; McRae-Clark, Aimee L.; Gray, Kevin M.; George, Mark S.; Brady, Kathleen T.
<x xml:space="preserve">Abstract</x> Background: Varenicline has been shown to reduce cigarette craving during a quit attempt. Objectives: Use BOLD fMRI to explore differences in smoking cue reactivity at baseline and after five weeks of varenicline smoking cessation treatment. Methods: Treatment-seeking nicotine-dependent adult smokers underwent BOLD fMRI scans with block presentation of visual smoking, neutral, and rest cues under two conditions: craving or resisting the urge to smoke at baseline and following 5 weeks of standard varenicline therapy. Data were analyzed using FMRI Expert Analysis Tool, version 5.98 of Functional Magnetic Imaging of the Brain Software Library focused on the smoking vs. neutral cue contrast at the individual and group level, Z>2.3 with cluster threshold p=0.05. Results: Twenty-one participants were scanned at baseline and 16 completed the study; 10 were abstinent at the 2nd session, confirmed with urinary cotinine. In the Crave Condition no significant differences were found between the abstinent and non-abstinent groups at either time point. During the baseline Resist Condition, the abstinent group compared to the non-abstinent group demonstrated activation in a distributed network involved in alertness, learning and memory. Additionally, within the abstinent group, increased activation of the superior frontal gyrus was found at baseline compared to week 5. Conclusion: Successful smoking cessation with varenicline is associated with increased activation, prior to a quit attempt, in brain areas related to attentiveness and memory while resisting the urge to smoke Scientific Significance: Varenicline may exert effects by both reducing craving and enhancing resistance to smoking urges during cue-elicited craving.